Actividad diurética de la Cecropia obtusifolia (Moraceae) en ratas albinas - Vargas Howell, Roberto (1996)
The possible diuretic effect of the !eaf extract of Cecropia obtusifolia, Berto!; used in Costa Rican traditional medicine, was tested on five Sprague Dawley rats in individual metabolic cages. During the control week, distilIed water was administered with ail intragastric cannula. During the C.obtusifolia week, the rats were given tbe aqueous leaf extrae! in a daily dosage of 500 mglkg , intragastricly. Although, tbe urinary flow was increased (p<0.05) by a 20%, there was no statistieally significant difference between tbe following parameters: excretion in urine of osmoles, sodium and potassium; daily ingestion of food and water. The animal weights decreased when C. obtusifolia was used, but only on the fourth day the deerease was significant